HERBAL SPECIES DIVERSITY IN PUTROE ALOEH TOURISM AREA, JEUMPA DISTRICT, SOUTHWEST ACEH REGENCY - Vivera Ruselli Puspa; Miftahul Munawwarah; Djufri Djufri; Wardiah Wardiah; Safrida Safrida; Muhibbuddin Muhibbuddin (Universitas Islam Negeri Ar-Raniry, 2023)
The presence of vegetation in an area will positively impact the balance of the ecosystem on a broader scale. Herbs play an important role in maintaining vegetation conditions and cycling of plant growth in an area. The study aimed to determine the composition of vegetation, important values , and diversity index (Ĥ) of herbs in the Putroe Aloeh Tourism Area, Jeumpa District, and Southwest Aceh District. The method used is the observation method with the subjective determination of stations and plots using the quadratic method. Research stations as many as seven include; the downstreams left side of the river, the downstream right side of the river, the left middle side of the river, the middle right side, of the river the upstream left side of the river, the upstream right side of the river, and the surrounding forest. Each station is placed in 10 square plots measuring 2 x 2 m. Parameters observed include; absolute density (KM) of species, absolute frequency (FM) of species, and absolute dominance (DM) of species. Data analysis included the Important Value (IV) of species’ Important Value (IV) y Index (Ĥ). Based on the research results, it is known that there are 50 herb species consisting of 26 families. The dominating family is Asteraceae (20%). The species with the highest category of importance value was Selaginella doederleinii (IV = 48.48), while the species with the lowest category were Emilia sonchifolia and Cyperus strigosus (IV = 0.16). The diversity index of herbaceous species at the study site was medium (Ĥ= 2.43).